Honeycomb-shaped high-concentration NO2 adsorption trapping material as well as preparation method and application thereof

By loading high-silicon molecular sieve on the surface of the honeycomb carrier, a honeycomb-like high-concentration NO2 adsorption and capture material was prepared, which solved the problem of low NO2 exhaust purification and recovery efficiency in the prior art, and achieved efficient adsorption and long-life NO2 capture effect.

CN119549134APending Publication Date: 2025-03-04UNIV OF SCI & TECH BEIJING +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411893988.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively purify and recover high-concentrated NO2 exhaust gas, and the performance of zeolite molecular sieves in extreme environments is degraded, and the regeneration performance and service life of adsorbent materials are insufficient.

Method used

High silicon molecular sieve is used to load on the surface of the honeycomb carrier, and the adsorption site of NO2 molecules on the surface is improved by preparing honeycomb-like high-concentration NO2 adsorption capture materials.

Benefits of technology

It achieves efficient capture and purification of high-concentration NO2, extends the service life of the material, improves the adsorption and capture efficiency, and reduces the cost of NO2 acquisition and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549134A_ABST
    Figure CN119549134A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of gas technical purification, and particularly relates to a honeycomb-shaped high-concentration NO2 adsorption trapping material as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) preparing adsorbent slurry by taking high-silicon molecular sieve raw powder as a raw material; (2) putting a honeycomb carrier into the adsorbent slurry for dipping and coating; and (3) naturally airing, drying and roasting the impregnated carrier to obtain the integral honeycomb-shaped high-concentration NO2 adsorbing and trapping material. On the basis of the honeycomb-shaped high-concentration NO2 adsorption trapping material (the molecular sieve silica-alumina ratio is 1000-5000), NO2 is efficiently trapped through a pressure swing adsorption technology, meanwhile, the adsorbent subjected to adsorption saturation is reversibly regenerated, high-concentration NO2 desorbed gas is obtained, NO2 recycling is achieved, NOx tail gas of a nuclear industry post-treatment plant is recycled, and the purpose of recycling the NOx tail gas of the nuclear industry post-treatment plant is achieved. A stable NO2 gas source is provided for a spent fuel post-treatment main process, the dual requirements of NO2 raw material preparation and tail gas denitration of a post-treatment plant are met, and purification and recycling of NO2 are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of gas purification technology, and specifically relates to a honeycomb high-concentration NO2 adsorption and capture material and a preparation method and application thereof. Background Art

[0002] NO2 plays an important role in the reprocessing of spent fuel in the nuclear industry. On the one hand, multiple processes in the reprocessing process will release a large amount of high-concentration NO2 tail gas. Direct NO2 emissions are seriously harmful to the human body and the environment and urgently need to be purified. On the other hand, the reprocessing process requires a large amount of NO2 gas as an oxidant for the important element plutonium and a decomposer for hydrazine. It can be seen that NO2 gas is both an important raw material and a gaseous pollutant, but the current production cost of NO2 is high and the pollution is large. It can be seen that if the NO2 tail gas generated by the reprocessing plant is purified and NO2 is recycled and resourced, it can meet the dual needs of NO2 raw material production and tail gas denitrification in the reprocessing plant at the same time. The purification and resource utilization of NO2 is an urgent problem to be solved.

[0003] The key to recovering high-concentration NO2 by adsorption separation process is to find practical NO2 adsorbent materials, so as to achieve efficient capture of NO2 and regeneration of adsorbent materials. In actual industrial applications, the adsorbent material will be in a high-humidity and acidic environment for a long time, which will require it to have: ① strong acid resistance, which can resist the impact of the acidic environment in long-term applications; ② strong hydrophobicity, there is a high humidity in the tail gas, because H2O and NO2 are both polar small molecule gases with similar adsorption characteristics, the presence of H2O will form a competitive adsorption relationship with NO2, which will directly affect its performance; meeting strong acid resistance and hydrophobicity requires that the crystal form of the adsorbent material is complete and free of any defects; ③ capture and enrichment ability, which requires not only the ability to capture NO2, but also the ability to desorb and enrich NO2; ④ strong mechanical strength, when using pressure swing adsorption separation technology, it will be in a shorter time. Multiple adsorption and desorption cycles are carried out within a certain period of time, which will require the honeycomb material to have strong mechanical strength to avoid damage such as pore collapse, powderization and pore blockage caused by repeated adsorption and desorption; ⑤ High loading amount, the amount of adsorbent loaded on the surface of the honeycomb material will determine the strength of its adsorption capacity. The larger the loading amount, the more adsorbents on its surface will provide more adsorption sites, which will directly improve its adsorption and capture capacity; ⑥ Large-size preparation. In the actual industrial application environment, it is not only in a high-humidity and acidic environment, but also radioactive. Therefore, it is required that the honeycomb capture material can be quickly filled and replaced, that is, large-size honeycomb adsorption materials are prepared and directly hoisted into the adsorption tower. At the same time, large-size materials can be used for a longer time, avoiding short-term replacement.

[0004] At present, there are many types of NO2 adsorbents, such as activated carbon, MOFs, polyoxometalates, molecular sieves, etc., as shown in Table 1. However, in comprehensive comparison, zeolite molecular sieves have higher NO2 adsorption capacity, industrial desorption temperature and excellent cyclic regeneration performance, and have become the mainstream adsorbent for industrial NOx applications. Its advantages are: (1) good pore characteristics, excellent NO-NO2 oxidation and NO2 adsorption capacity; (2) suitable for industrial desorption temperature range (≤350℃); (3) excellent cyclic regeneration performance; (4) moderate cost investment. However, in current industrial applications, the main technical problems of zeolite molecular sieve adsorption of NO2 are: (1) while effectively adsorbing the target NO2 molecules, it will also adsorb non-target molecules, resulting in poor separation effect; (2) although zeolite molecular sieves are regenerable, in actual applications, their regeneration performance will be affected by many factors, such as regeneration conditions, which will in turn affect their service life; (3) under certain extreme environmental conditions, such as high temperature, high pressure, strong acid, strong alkali, etc., the structure and performance of zeolite molecular sieves will be affected, thereby reducing their adsorption and separation effects.

[0005] However, there are few studies on the adsorption and separation of high-concentration NO2 (0.5%-20%). It is not clear what kind of material is suitable for the adsorption and purification of high-concentration NO2 in post-treatment plants. There is a lack of data on the adsorption and desorption of high-concentration NO2. It is not clear what kind of material is suitable for the adsorption and purification of high-concentration NO2, and there is a lack of data on the adsorption and desorption of high-concentration NO2. It is not clear what the structure-activity relationship between the structure and performance of the adsorption material is, as well as the appropriate adsorption and desorption conditions (temperature, pressure, flow rate, etc.). Therefore, there is an urgent need to prepare honeycomb adsorption and capture materials for high-concentration NO2. Summary of the invention

[0006] In view of the above technical problems, the present invention provides a honeycomb high-concentration NO2 adsorption and capture material and a preparation method and application. The honeycomb high-concentration NO2 adsorption and capture material provided by the present invention loads a high-silicon molecular sieve on the surface of a honeycomb carrier for application, thereby improving the adsorption efficiency, increasing the adsorption sites of NO2 molecules on the surface of the material, and improving the adsorption and capture efficiency.

[0007] In order to achieve the above technical objectives, the present invention provides the following technical solutions:

[0008] A method for preparing a honeycomb high-concentration NO2 adsorption and capture material, the preparation method comprising:

[0009] (1) preparing an adsorbent slurry using high silicon molecular sieve powder as raw material;

[0010] (2) placing the honeycomb carrier into the adsorbent slurry for dipping and coating;

[0011] (3) The honeycomb carrier treated in step (2) is naturally aired, dried, and calcined to obtain an integral honeycomb high-concentration NO2 adsorption and capture material.

[0012] Furthermore, in step (1), the raw materials required for preparing the adsorbent slurry include, by weight: 100-1000 parts of water, 2.5-40 parts of thickener, 10-100 parts of binder, 10-100 parts of auxiliary agent, 50-400 parts of high-silicon molecular sieve raw powder and 1-10 parts of weak base reagent;

[0013] The method for preparing the adsorbent slurry is:

[0014] (1.1) Weigh 100-1000 parts of water, 2.5-40 parts of thickener, 10-100 parts of binder and 10-100 parts of auxiliary agent in order by mass, mix and stir to form an adsorbent aqueous solution;

[0015] (1.2) The adsorbent aqueous solution, 50-400 parts of high-silicon molecular sieve raw powder and 1-10 parts of weak base reagent are mixed and stirred to form the adsorbent slurry.

[0016] Furthermore, the high-silicon molecular sieve includes any one or more of CHA, BETA, FAU and ZSM-5 zeolites; and the silicon-aluminum ratio of the high-silicon molecular sieve is 1000-5000, and the grain size is 1-5 μm. After testing, the specific surface area of ​​the high-silicon molecular sieve used in the present invention is 300-800m 2 / g, pore volume range is 0.40-0.80cm 3 / g, pore size is 0.34-2nm.

[0017] Further, the thickener is any one of hydroxypropyl methylcellulose, carboxymethyl cellulose, and industrial soluble starch; the binder is any one of aluminum sol, attapulgite, and silica sol; the auxiliary agent is any one of ethylenediamine, ammonia water, isopropanolamine, and monoethanolamine; the weak base reagent is any one of ammonia water, copper hydroxide, and iron hydroxide;

[0018] In the present invention, a binder is used to enhance the loading effect of the adsorbent slurry; an auxiliary agent can prevent the adsorbent from agglomerating, keep the slurry stable, and prevent the slurry from stratifying; a thickener increases the viscosity of the slurry, increases the adsorbent coating loading, and prevents the adsorbent from falling off the carrier; a weak alkaline reagent is used to adjust the pH value of the adsorbent slurry to be weakly alkaline, which can make it easier to capture high-concentration NO2 gas in a weakly alkaline environment.

[0019] The viscosity of the adsorbent slurry is controlled to be between 20 and 50 mPa·s, and the pH of the adsorbent slurry is controlled to be between 7.0 and 8.5.

[0020] In the present invention, the viscosity and pH value of the adsorbent slurry need to be strictly controlled. The viscosity needs to be moderate, and the viscosity is controlled at 20-50 mPa·s, thereby controlling the loading amount of the final honeycomb high-concentration NO2 adsorption capture material to be controlled at 240-450 kg / m3 ; The pH value needs to be moderate, and the pH value should be controlled at 7.0-8.5. If the slurry viscosity is too high, although the load capacity will increase, the slurry fluidity is extremely poor, and the pores of the entire honeycomb carrier will be completely blocked; if the slurry viscosity is too low, the amount of slurry loaded on the honeycomb carrier is extremely low, resulting in a low load capacity and poor adsorption and desorption effect. If the slurry pH value is too small, it is not conducive to promoting the adsorption and capture of high-concentration NO2; if the slurry pH value is too high, although it promotes adsorption and capture, it is difficult to desorb and recover high-concentration NO2.

[0021] Furthermore, in step (2), the honeycomb carrier is pretreated and then dip-coated;

[0022] The pretreatment specifically includes: cutting the honeycomb carrier into the required shape, placing the cut honeycomb carrier into a muffle furnace and heating it to 350-500°C for pretreatment; the treatment time range is 5-20h; the technical effect of this step is: the high temperature of 350-500°C can burn the organic glue inside the honeycomb carrier, and the entire carrier becomes looser after pretreatment. The pretreated carrier is dipped and coated, and more adsorbent slurry can be loaded. Since the adsorbent slurry has a certain viscosity, drying and roasting after coating can obtain a honeycomb high-concentration NO2 adsorption and capture material with a certain strength.

[0023] In step (2), the honeycomb carrier is placed in the adsorbent slurry for immersion coating for 5-30 minutes.

[0024] Furthermore, step (3) is specifically as follows: leaving the impregnated carrier to air-dry for 1-24 hours, drying at 100-250°C for 1-10 hours, and calcining at 200-450°C for 2-40 hours to obtain an integral honeycomb high-concentration NO2 adsorption and desorption material.

[0025] A large amount of slurry will adhere to the surface and internal pores of the honeycomb carrier after impregnation. The slurry is fluid, so the purpose of leaving the impregnated carrier vertically and naturally for a period of time is to allow the unloaded slurry on the carrier to flow out of the carrier naturally, avoiding the slurry blocking the pores, which will affect its adsorption and desorption effect (if a pore is blocked, this pore cannot adsorb NO2 gas during gas adsorption due to blockage, and the pore loses its role).

[0026] The purpose of drying is to remove the moisture inside the carrier to make the overall strength higher and avoid damage and powder loss of the carrier due to bumps and other reasons.

[0027] The purpose of roasting is the same as that of pretreatment. The raw materials added to prepare the slurry contain some organic glue. Roasting is also to burn out the organic glue inside the carrier, provide more pores for the adsorbent, and increase its adsorption capacity. Because the adsorbent slurry has been loaded onto the honeycomb carrier, the carrier still has strength after roasting.

[0028] A honeycomb high-concentration NO2 adsorption and capture material, comprising a honeycomb carrier and a high-silicon molecular sieve loaded on the honeycomb carrier; the high-silicon molecular sieve comprises any one or more of CHA type, BETA type, FAU type and ZSM-5 type zeolites, and the silicon-aluminum ratio of the high-silicon molecular sieve is 1000-5000, and the grain size is 1-5μm.

[0029] Furthermore, the honeycomb high-concentration NO2 adsorption and capture material is a large-sized cylinder with a cross-sectional diameter of 0.1-1m, a height of 0.1-1m, and a honeycomb hole equivalent diameter of 1-3mm. The integral large-sized honeycomb high-concentration NO2 adsorption and capture material is hoisted into the adsorption tower and used for NO2 tail gas treatment in nuclear industry post-processing plants to carry out NO x The recovery and reuse of tail gas meets the dual needs of NO2 raw material production and tail gas denitrification in the post-processing plant, realizing the purification and resource utilization of NO2; the integral large-size honeycomb high-concentration NO2 adsorption and capture material facilitates the replacement of adsorption materials and improves production efficiency.

[0030] An application of a honeycomb high-concentration NO2 adsorption and capture material, wherein the honeycomb high-concentration NO2 adsorption and capture material is used for separating high-concentration NO2 in flue gas by pressure-temperature swing adsorption, wherein the volume percentage concentration of NO2 in the flue gas is 0.5%-20%.

[0031] The application of high-silicon molecular sieve honeycomb is to use high-silicon ZSM-5 molecular sieve for pressure and temperature swing adsorption separation of high-concentration NO2. The high-silicon molecular sieve includes CHA type, BETA type, FAU type and ZSM-5 type zeolite, and the silicon-aluminum ratio of the high-silicon molecular sieve is 1000-5000, and the grain size is 1-5μm.

[0032] The beneficial effects of the present invention are:

[0033] (1) The high silicon molecular sieve raw powder with a silicon-aluminum ratio of 1000-5000 selected by the present invention has excellent NO2 adsorption and desorption performance parameters (including penetration adsorption amount and desorbed NO2 instantaneous concentration); and the present invention loads the high silicon molecular sieve on the surface of a honeycomb carrier to prepare a honeycomb high-concentration NO2 adsorption and capture material for application, which has more advantages than the high silicon molecular sieve raw powder, mainly reflected in five aspects: ① lower pressure drop; ② fast adsorption rate; ③ no pulverization phenomenon; ④ in practical applications, the filling and replacement of the molecular sieve are more convenient; ⑤ the occurrence of disproportionation reaction is avoided to a large extent; and the NO2 adsorption and capture material provided by the present invention adopts a high silicon molecular sieve with a silicon-aluminum ratio of 1000-5000 to prepare the adsorbent slurry, which can improve the hydrophobic performance of the NO2 adsorption and capture material, because: 1) the increase in silicon content increases the number of silicon-oxygen bonds, and the silicon-oxygen bonds are stronger than the aluminum-oxygen bonds, forming a more stable skeleton structure, thereby reducing the number of hydrophilic groups Si-OH; 2) the Si-OH groups on the surface of the molecular sieve decrease, while the Si-O-Si groups increase. Si-OH is a hydrophilic group, and its reduction directly leads to an increase in hydrophobicity; 3) The high silicon-aluminum ratio makes the pore size of the molecular sieve smaller, the pores narrower, and it is more difficult for water molecules to enter;

[0034] (2) The NO2 adsorption and capture material provided in the present invention has a honeycomb structure, a higher specific surface area and a more optimized pore size distribution, providing more adsorption space, so that the material can be better dispersed and withstand corrosion when in contact with acidic substances, thereby extending the service life, so that it can maintain the stability of structure and performance in an acidic environment. At the same time, its regular honeycomb structure and uniform pore size help to reduce the competitive adsorption of water molecules on the adsorbent surface, thereby improving hydrophobicity. In addition, the honeycomb high-concentration NO2 adsorption and capture material provided by the present invention loads high-silicon molecular sieves on the surface of the honeycomb carrier for application, improves the adsorption efficiency, increases the adsorption sites of NO2 molecules on the surface of the material, and improves the adsorption and capture efficiency. The honeycomb adsorbent has a porous, high-specific surface area honeycomb structure, which increases the adsorption area and provides more adsorption sites, thereby improving the adsorption efficiency; its pore size distribution is reasonable, which is conducive to the diffusion and transmission of adsorbate molecules, further improving the adsorption performance.

[0035] (3) The service life of the honeycomb high-concentration NO2 adsorption and capture material provided by the present invention is greatly improved. The penetration adsorption amount after 10 adsorption and desorption cycles is stabilized at about 0.4 mmol / g, and the desorbed gas concentration is stabilized at about 10%, which is nearly 4 times higher than the exhaust gas concentration.

[0036] (4) The honeycomb-shaped high-concentration NO2 adsorption and capture material provided by the present invention can be used to directly prepare large-size honeycomb materials (cross-sectional diameter is 0.1-1m, height is 0.1-1m, and honeycomb hole equivalent diameter is 1-3mm) for actual industrial applications, namely, exhaust gas treatment in nuclear industry post-processing plants. It can realize the recovery and reuse of nitrogen oxide-containing exhaust gas in post-processing plants, greatly reduce the acquisition cost and environmental protection cost of NO2, and at the same time meet the dual needs of NO2 raw material production and exhaust gas denitrification in post-processing plants, thereby realizing NO2 purification and resource utilization.

[0037] (5) The honeycomb high-concentration NO2 adsorption and capture material provided by the present invention can efficiently capture NO2 through pressure swing adsorption technology, and at the same time, can reversibly regenerate the adsorbent after adsorption saturation to obtain high-concentration NO2 desorption gas, thereby realizing NO2 resource utilization, so as to realize the recovery and reuse of nitrogen oxide tail gas in nuclear industry reprocessing plants, provide a stable NO2 gas source for the main process of spent fuel reprocessing, meet the dual needs of NO2 raw material preparation and tail gas denitrification in the reprocessing plant, reduce the emission of nitrogen oxides, radioactive waste liquid and non-nitrate waste liquid in the spent fuel reprocessing plant, and greatly reduce the cost of obtaining NO2 and the environmental protection cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a scanning electron microscope (SEM) characterization image of No. 1 high-silicon molecular sieve raw powder at a scale of 10 μm;

[0039] Figure 2 This is a scanning electron microscope (SEM) characterization image of No. 2 high-silicon molecular sieve raw powder at a scale of 10 μm;

[0040] Figure 3 This is a scanning electron microscope (SEM) characterization image of No. 3 high-silicon molecular sieve raw powder at a scale of 10 μm;

[0041] Figure 4 This is a scanning electron microscope (SEM) characterization image of No. 4 high-silicon molecular sieve raw powder at a scale of 10 μm;

[0042] Figure 5 This is a scanning electron microscope (SEM) characterization image of No. 5 high-silicon molecular sieve raw powder at a scale of 10 μm;

[0043] Figure 6 The static water vapor adsorption characterization results of No. 1-5 high silicon molecular sieve raw powder;

[0044] Figure 7 The static water vapor adsorption characterization results of No. 1 high-silicon molecular sieve raw powder and the honeycomb adsorption and capture material prepared therefrom (Example 1);

[0045] Figure 8The results of the test on the effect of desorption pressure and purge gas flow rate on desorption performance during pressure swing adsorption;

[0046] Fig. 9 This is a physical picture of the large-sized honeycomb high-concentration NO2 adsorption and capture material used for exhaust gas treatment in nuclear industry reprocessing plants. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further described below in conjunction with specific embodiments and drawings.

[0048] Preliminary performance tests were carried out on CHA, BETA, FAU, ZSM-5, MFI, HEU, LTA, MOR, and FER zeolite molecular sieves to compare their adsorption and desorption performances, as shown in Table 1.

[0049] Table 1 Comparison of the basic performance test results of zeolite molecular sieves;

[0050]

[0051] In Table 1, q b Refers to the penetration adsorption during the adsorption process, q b1 ,q b2 ,q b3 Respectively represent the breakthrough adsorption amount C in the first, second and third adsorption processes NO2 , max refers to the maximum concentration of NO2 gas desorbed during the desorption process, which is directly measured by the flue gas analyzer. C1, C2, and C3 represent the maximum concentration of NO2 gas during the first, second, and third desorption processes, respectively. A comprehensive comparison of the above nine zeolite molecular sieve samples shows that the adsorption amount of CHA, BETA, FAU, and ZSM-5 molecular sieves during the first, second, and third adsorption processes is at a relatively high level, and at the same time, the first, second, and third desorptions can desorb a relatively high concentration of NO2 gas; and the test results of MFI, HEU, LTA, MOR, and FER zeolite molecular sieves show that the adsorption amount of these zeolites is extremely small and penetration occurs immediately in a relatively short time, and the concentration of the desorbed gas is relatively low, which is 2.5% lower than the intake concentration of the raw gas, and the adsorption and desorption effect is poorer than that of CHA, BETA, FAU, and ZSM-5 molecular sieves. Therefore, the high silicon molecular sieve used in the present invention includes any one or more of CHA, BETA, FAU, and ZSM-5 zeolites.

[0052] Taking ZSM-5 zeolite molecular sieve as an example, the NO2 adsorption performance of molecular sieves with different silicon-aluminum ratios is tested. Five ZSM-5 zeolite molecular sieve samples with different silicon-aluminum ratios (numbered 1, 2, 3, 4, and 5) are selected to test their basic performance. In the present invention, the silicon-aluminum ratio refers to the molar ratio of SiO2 and Al2O3; as shown in Table 2, combined with relevant characterization methods, the molecular sieve raw powder is optimized and the preparation of the integral honeycomb molecular sieve is studied.

[0053] Table 2 Comparison of basic performance test results of 5 zeolite molecular sieve raw powders;

[0054]

[0055] Experimental results analysis:

[0056] ⑴Comparing the first adsorption and desorption of each material, only samples 1-3 have an adsorption amount greater than 1.00mmol / g, and only samples 1 and 2 have a high concentration of NO2 gas desorbed under negative pressure conditions. The desorbed gas concentration of samples 3-5 is low, below 2%, which is 2.5% lower than the actual gas source concentration. Therefore, only sample 1 showed good adsorption and desorption performance in the first adsorption and desorption;

[0057] ⑵Compared with the second adsorption and desorption, the adsorption amount has decreased significantly compared with the first one. The main reason for this is that the desorption was not complete during the first desorption process, resulting in some NO2 still occupying the adsorption sites on the molecular sieve, thus affecting the second adsorption process. The samples with higher adsorption amounts are No. 1 and No. 2, with the highest being 0.39mmol / g for No. 1. At the same time, the desorption gas concentrations of No. 1 and No. 2 are also high and stable, and the desorption gas concentrations of No. 3-5 samples have decreased again. In terms of the adsorption and desorption effects, No. 1 and No. 2 samples showed better results in the second adsorption and desorption process, that is, they have a higher level of adsorption and desorption capabilities.

[0058] ⑶ Compared with the third adsorption and desorption, the penetration adsorption amount of samples 3-5 continued to decline significantly, while the adsorption amount of samples 1 and 2 was relatively stable, proving that their adsorption performance tended to be stable with the cycle of adsorption and desorption, while the desorption performance of samples 3-5 was relatively poor, indicating that the service life of samples 3-5 was seriously affected with the progress of the adsorption and desorption cycle, and the material was deactivated in a relatively short time. Overall, the adsorption and desorption performance of sample 1 ranked first, followed by sample 2, both of which showed good performance.

[0059] Comprehensively comparing the above five samples, the adsorption amounts of samples 1 and 2 were at a relatively high level during the first, second and third adsorption processes, and they were able to desorb higher concentrations of NO2 gas during the first, second and third desorptions. Moreover, as the adsorption and desorption cycles proceeded, their performance became more stable and more suitable for practical applications.

[0060] The above five ZSM-5 zeolite molecular sieve raw powders were subjected to in-situ characterization technology tests such as SEM, ICP-MS, BET, and static water vapor adsorption to gain an in-depth understanding of their internal structure, basic parameters / performance, etc.

[0061] (1)ICP-MS and BET characterization:

[0062] The silicon-aluminum ratio of the molecular sieve was tested by ICP-MS characterization, and the specific surface area, pore size and pore volume of the molecular sieve were tested by BET characterization. As shown in Table 3, among the five samples, sample No. 1 has the largest silicon-aluminum ratio, the smallest crystal grains, and the largest specific surface area, but its pore size is relatively small; sample No. 2 is second. The silicon-aluminum ratio has the most direct impact on its adsorption and desorption performance. At the same time, the large specific surface area provides sufficient adsorption sites and channels for the adsorption of NO2. The pore system of high-silicon molecular sieves No. 1 and No. 2 has a smaller pore diameter, which gives it excellent selectivity, which means that only molecules smaller than the crystal pores (such as NO2) can enter the adsorption site; therefore, the grain size of the high-silicon molecular sieve used in the present invention is limited to 1-5μm.

[0063] Table 3 ICP-MS and BET characterization of five ZSM-5 zeolite molecular sieves with different silicon-aluminum ratios

[0064]

[0065] (2) SEM characterization:

[0066] like Figure 1-5 , SEM characterization shows that the No. 1 molecular sieve sample has a relatively high silicon-aluminum content, its internal crystal form is relatively regular, the grain size is consistent, the arrangement is orderly, and there is no aggregation; the No. 2 molecular sieve grains are partially aggregated and the size is relatively consistent, while the No. 3-5 molecular sieve samples have a relatively low silicon-aluminum content, and their grains are seriously aggregated, with different sizes and disordered arrangement. The grains are stacked and aggregated, which will greatly reduce the number of adsorption sites on its surface, thereby directly affecting its adsorption and desorption performance.

[0067] (3) Static water vapor adsorption characterization:

[0068] like Figure 6As shown in the figure, the water absorption performance of samples 1 and 2 is poor, while their hydrophobic performance is good. In the actual application environment, there is high humidity. In order to avoid the competitive adsorption relationship between H2O molecules and NO2, molecular sieve materials with good hydrophobicity and good nitro affinity are needed.

[0069] By adopting the above method and combining it with relevant characterization methods, the present invention conducts experiments on molecular sieve raw powder with a silicon-aluminum ratio of 1000-5000. The experimental results show that when the silicon-aluminum ratio is 1000-5000 and the grain size is 1-5μm, the molecular sieve has a better adsorption effect on NO2 gas and a higher concentration of desorbed enriched gas. It is suitable for the adsorption, purification, capture and recovery of high-concentration NO2, and can realize the purification and resource utilization of NO2. The following are specific embodiments.

[0070] Example 1: A method for preparing a honeycomb-shaped high-concentration NO2 adsorption and capture material: comprising:

[0071] Weigh 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent in order by mass, mix and stir to form an aqueous solution; mix the obtained adsorbent aqueous solution with 150 parts of sample No. 1 and 3 parts of weak base reagent, and mechanically stir for 10-30 hours to obtain an adsorbent slurry with a viscosity of 30 mPa·s and a pH of 7.9;

[0072] The honeycomb carrier is cut into the required shape, and the cut honeycomb carrier is placed in a muffle furnace and heated to 350-500℃ for 5-20h pretreatment; the pretreated honeycomb carrier is placed in the adsorbent slurry for immersion coating for 5-30min; the impregnated carrier is left to air for 1-24h, dried at 100-250℃ for 1-10h, and calcined at 200-450℃ for 2-40h, and finally a loading capacity of 330kg / m can be obtained. 3 Honeycomb high-concentration NO2 adsorption and capture material.

[0073] In this embodiment, the performance of the prepared honeycomb high-concentration NO2 adsorption and capture material was tested. The test experimental conditions are: adsorption temperature is 20-50°C (preferably 30°C), intake air flow rate is 3-6.25L / min (preferably 5L / min), NO2 concentration is 2.5%, relative humidity is 20%-80% (preferably 60%); desorption temperature is 20-50°C (preferably 30°C), purge gas flow rate is 0.5-3L / min (preferably 1L / min), and desorption pressure is -90kPa--97kPa (preferably -95kPa).

[0074] Embodiment 2:

[0075] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 100 parts of binder and 35 parts of auxiliary agent are weighed in sequence by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of sample No. 2 and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 38 mPa·s and a pH of 7.2.

[0076] Embodiment 3:

[0077] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in sequence by mass and mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of sample No. 3 and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 46 mPa·s and a pH of 7.8.

[0078] Embodiment 4:

[0079] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of sample No. 4 and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 53.5 mPa·s and a pH of 8.6.

[0080] Embodiment 5:

[0081] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in sequence by mass and mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of sample No. 5 and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 64 mPa·s and a pH of 9.5.

[0082] Embodiment 6:

[0083] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of ZSM-5 molecular sieve raw powder (Si / Al=2608.20) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 32 mPa·s and a pH of 7.7.

[0084] Embodiment 7:

[0085] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of ZSM-5 molecular sieve raw powder (Si / Al=3740.16) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 29 mPa·s and a pH of 8.0.

[0086] Embodiment 8:

[0087] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of ZSM-5 molecular sieve raw powder (Si / Al=4996.12) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 28 mPa·s and a pH of 8.0.

[0088] According to the test conditions in Example 1, the honeycomb high-concentration NO2 adsorption capture materials obtained in Examples 1-8 were tested, and the experimental results are shown in Table 4. According to the experimental results in Table 4, the honeycomb high-concentration NO2 adsorption capture material prepared by using No. 1 molecular sieve in Example 1 has better adsorption and desorption performance than the original powder material of No. 1 molecular sieve, and its adsorption and desorption performance has been improved. At the same time, its hydrophobic performance has also been improved. Figure 7 , it can be seen that the overall performance of the honeycomb material is better than that of the original powder. Although the adsorption and desorption performance of the honeycomb high-concentration NO2 adsorption and capture material prepared by Example 3-5 using molecular sieve sample No. 3-5 (silicon-aluminum ratio less than 1000) is better than that of the molecular sieve original powder, it is still poorer than the molecular sieve with a silicon-aluminum ratio greater than 1000. At the same time, its load is large, resulting in partial pore blockage on the surface of the material, resulting in low penetration adsorption and desorption enrichment gas concentrations. In contrast to Examples 1, 2, 6-8, the silicon-aluminum ratio of the ZSM-5 molecular sieve used is between 1000 and 5000. As the silicon-aluminum ratio increases, its adsorption and desorption performance gradually increases. It can be seen that when the silicon-aluminum ratio is 1000-5000, the molecular sieve has a better adsorption effect on NO2 gas, and is suitable for adsorption, purification, capture and recovery of high-concentration NO2.

[0089] Table 4 Adsorption and desorption experimental results of Examples 1-8;

[0090]

[0091] Embodiment 9:

[0092] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of CHA type molecular sieve raw powder (Si / Al=5009.02) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 28.5 mPa·s and a pH of 8.2.

[0093] Embodiment 10:

[0094] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of CHA type molecular sieve raw powder (Si / Al=3512.10) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 30 mPa·s and a pH of 8.1.

[0095] Embodiment 11:

[0096] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of CHA type molecular sieve raw powder (Si / Al=2488.26) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 36.5 mPa·s and a pH of 7.9.

[0097] Embodiment 12:

[0098] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of CHA type molecular sieve raw powder (Si / Al=1021.74) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 42 mPa·s and a pH of 7.7.

[0099] Embodiment 13:

[0100] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of CHA type molecular sieve raw powder (Si / Al=556.44) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 50.5 mPa·s and a pH of 7.4.

[0101] According to the test conditions in Example 1, the honeycomb high-concentration NO2 adsorption and capture materials obtained in Examples 9-13 were tested, and the experimental results are shown in Table 5; According to the experimental results in Table 5, Examples 9-13 all use CHA type molecular sieve raw powder (different silicon-aluminum ratios) to prepare honeycomb high-concentration NO2 adsorption and capture materials, and their adsorption and desorption performance gradually increases with the increase of the silicon-aluminum ratio. When the silicon-aluminum ratio of the CHA type molecular sieve is between 1000 and 5000, its molecular sieve has a better adsorption effect on NO2 gas, which is consistent with the performance of the ZSM-5 type molecular sieve.

[0102] Table 5 Adsorption and desorption experimental results of Examples 9-13;

[0103]

[0104] Embodiment 14:

[0105] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of BETA molecular sieve raw powder (Si / Al=4846.21) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 26.5 mPa·s and a pH of 8.3.

[0106] Embodiment 15:

[0107] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of BETA molecular sieve raw powder (Si / Al=3498.46) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 30.5 mPa·s and a pH of 8.0.

[0108] Embodiment 16:

[0109] The other operating steps in this embodiment are the same as those in Embodiment 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of BETA molecular sieve raw powder (Si / Al=2112.02) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 37 mPa·s and a pH of 7.7.

[0110] Embodiment 17:

[0111] The other operating steps in this embodiment are the same as those in Embodiment 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of BETA molecular sieve raw powder (Si / Al=998.31) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 52.5 mPa·s and a pH of 7.1.

[0112] Embodiment 18:

[0113] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of BETA molecular sieve raw powder (Si / Al=442.20) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 52.5 mPa·s and a pH of 7.1.

[0114] According to the test conditions in Example 1, the honeycomb high-concentration NO2 adsorption and capture materials obtained in Examples 14-18 were tested, and the experimental results are shown in Table 6; According to the experimental results in Table 6, Examples 14-18 all use BETA molecular sieve raw powder (different silicon-aluminum ratios) to prepare honeycomb high-concentration NO2 adsorption and capture materials, and their adsorption and desorption performance gradually increases with the increase of silicon-aluminum ratio, which is consistent with the performance of ZSM-5 and CHA molecular sieves. When the silicon-aluminum ratio of the BETA molecular sieve is between 1000 and 5000, its molecular sieve has a better adsorption effect on NO2 gas.

[0115] Table 6 Adsorption and desorption experimental results of Examples 14-18;

[0116]

[0117] Embodiment 19:

[0118] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of FAU molecular sieve raw powder (Si / Al=5022.21) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 25.5 mPa·s and a pH of 8.3.

[0119] Embodiment 20:

[0120] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of FAU molecular sieve raw powder (Si / Al=3886.41) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 31 mPa·s and a pH of 8.0.

[0121] Embodiment 21:

[0122] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of FAU molecular sieve raw powder (Si / Al=1922.76) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 39 mPa·s and a pH of 7.6.

[0123] Embodiment 22:

[0124] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of FAU molecular sieve raw powder (Si / Al=1089.53) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 51 mPa·s and a pH of 7.3.

[0125] Embodiment 23:

[0126] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of FAU molecular sieve raw powder (Si / Al=604.21) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 51 mPa·s and a pH of 7.3.

[0127] According to the test conditions in Example 1, the honeycomb high-concentration NO2 adsorption and capture materials obtained in Examples 19-23 were tested, and the experimental results are shown in Table 7; According to the experimental results in Table 7, Examples 19-23 all use FAU type molecular sieve raw powder (different silicon-aluminum ratios) to prepare honeycomb high-concentration NO2 adsorption and capture materials, and their adsorption and desorption performance gradually increases with the increase of silicon-aluminum ratio, which is consistent with the performance of ZSM-5 type, CHA type, and BETA type molecular sieves. When the silicon-aluminum ratio of the FAU type molecular sieve is between 1000 and 5000, its molecular sieve has a better adsorption effect on NO2 gas.

[0128] Table 7 Adsorption and desorption experimental results of Examples 19-23;

[0129]

[0130] Embodiment 24:

[0131] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of ZSM molecular sieve raw powder (grain size 6.5 μm) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 55 mPa·s and a pH of 6.9.

[0132] Embodiment 25:

[0133] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of ZSM molecular sieve raw powder (grain size 5.2 μm) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 49 mPa·s and a pH of 7.2.

[0134] Embodiment 26:

[0135] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of ZSM molecular sieve raw powder (grain size 4.3 μm) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 40.5 mPa·s and a pH of 7.5.

[0136] Embodiment 27:

[0137] The other operating steps in this embodiment are the same as those in Embodiment 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of ZSM molecular sieve raw powder (grain size 1.1 μm) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 28 mPa·s and a pH of 7.9.

[0138] Embodiment 28:

[0139] The other operating steps in this embodiment are the same as those in Example 1, except that, 300 parts of water, 10.5 parts of thickener, 30 parts of binder and 35 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 150 parts of ZSM molecular sieve raw powder (grain size 0.5 μm) and 3 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 20 mPa·s and a pH of 8.3.

[0140] According to the test conditions in Example 1, the honeycomb high-concentration NO2 adsorption and capture materials obtained in Examples 24-27 were tested, and the experimental results are shown in Table 8; According to the experimental results in Table 8, Examples 24-27 all use ZSM-type molecular sieve raw powder (different grain sizes) to prepare the honeycomb high-concentration NO2 adsorption and capture materials, and their adsorption and desorption performance gradually increases with the decrease of the grain size. This is because the smaller the grain of the adsorbent, the larger its surface area, which can provide more adsorption sites, thereby improving the adsorption efficiency; and if the grain is too small, it is easy to agglomerate or clog during operation, thereby affecting the adsorption effect. When the grain size of the ZSM-5 molecular sieve is 1-5μm, the molecular sieve has a better adsorption effect on NO2 gas. At the same time, by testing the CHA, BETA, and FAU molecular sieves, the results are consistent with the performance of the ZSM-5 molecular sieve. The smaller the grain, the better the adsorption effect.

[0141] Table 8 Example 1, 24-28 adsorption and desorption experimental results;

[0142]

[0143]

[0144] Embodiment 29:

[0145] The other operating steps in this embodiment are the same as those in Example 1, except that, 100 parts of water, 2.5 parts of thickener, 10 parts of binder and 10 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 50 parts of sample No. 1 and 2 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 40.5 mPa·s and a pH of 7.8.

[0146] Embodiment 30:

[0147] The other operating steps in this embodiment are the same as those in Example 1, except that, 500 parts of water, 10 parts of thickener, 60 parts of binder and 20 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 60 parts of sample No. 1 and 1 part of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 21.5 mPa·s and a pH of 7.2.

[0148] Embodiment 31:

[0149] The other operating steps in this embodiment are the same as those in Example 1, except that, 200 parts of water, 10.5 parts of thickener, 100 parts of binder and 100 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 400 parts of sample No. 1 and 10 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 48.0 mPa·s and a pH of 8.3.

[0150] Embodiment 32:

[0151] The other operating steps in this embodiment are the same as those in Example 1, except that 900 parts of water, 9 parts of thickener, 80 parts of binder and 60 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 200 parts of sample No. 1 and 5 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 22.0 mPa·s and a pH of 7.3.

[0152] Embodiment 33:

[0153] The other operating steps in this embodiment are the same as those in Example 1, except that, 500 parts of water, 6 parts of thickener, 20 parts of binder and 40 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 250 parts of sample No. 1 and 7 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 38.5 mPa·s and a pH of 8.2.

[0154] Embodiment 34:

[0155] The other operating steps in this embodiment are the same as those in Example 1, except that, 800 parts of water, 5 parts of thickener, 50 parts of binder and 55 parts of auxiliary agent are weighed in order by mass, mixed and stirred to form an aqueous solution; the obtained adsorbent aqueous solution is mixed with 200 parts of sample No. 1 and 9 parts of weak base reagent, and mechanically stirred for 10-30 hours to obtain an adsorbent slurry with a viscosity of 27 mPa·s and a pH of 8.0.

[0156] According to the test conditions in Example 1, the honeycomb high-concentration NO2 adsorption and capture materials obtained in Examples 29-34 were tested, and the experimental results are shown in Table 9; According to the experimental results in Table 9, it can be seen that, calculated by mass, according to 100-1000 parts of water, 2.5-40 parts of thickener, 10-100 parts of binder, 10-100 parts of auxiliary agent, 50-400 parts of high-silicon molecular sieve raw powder and 1-10 parts of weak base reagent, the adsorbent slurry prepared by the above formula configuration and then coated can achieve higher adsorption capacity and desorption gas concentration.

[0157] Table 9: Adsorption and desorption experimental results of Examples 1, 29-34;

[0158]

[0159] According to the test conditions in Example 1, the honeycomb high-concentration NO2 adsorption and capture material obtained in Example 1 was subjected to multiple adsorption and desorption cycle tests, and the experimental results are shown in Table 10; according to the experimental results in Table 15, the honeycomb high-concentration NO2 adsorption and capture material prepared by coating the adsorbent slurry prepared according to Example 1 with high silicon molecular sieve, i.e., sample No. 1 (silicon-aluminum ratio = 2010.06) still had a relatively high and stable adsorption capacity and desorbed enriched gas concentration during 10 adsorption and desorption cycles, showing strong cyclic stability and service life of the molecular sieve (10 adsorption and desorption tests have proved the stability and service life of the adsorbent).

[0160] Table 10 Multiple adsorption and desorption experimental results of Example 1;

[0161]

[0162] During the pressure swing adsorption process, the adsorption process is usually carried out at room temperature and pressure. High temperature and high pressure will inhibit the adsorption; while the desorption needs to be carried out under vacuum conditions. The pressure change and the change of the purge gas flow rate will affect the NO2 concentration of the desorbed gas, such as Figure 8 In (a)(b), the concentration of desorbed gas changes with the change of pressure and purge gas flow rate. When the desorption pressure is lower than -90kPa, the concentration of desorbed gas NO2 shows a lower level, while when the desorption pressure is between -90kPa and -93kPa, the concentration of desorbed gas can show a higher level. After a large number of experimental verifications, it is found that in the actual application process, the filling of the honeycomb molecular sieve and the process conditions in the specific application are involved. When filling, the molecular sieve channel side needs to face the gas source, and the size of the honeycomb molecular sieve needs to fit the inner size of the adsorption tower to ensure that the gas source flows through the honeycomb molecular sieve; the adsorption process is usually carried out at room temperature and pressure, and the desorption needs to be carried out under vacuum conditions (-90 to -97kPa), accompanied by purge gas (the purge gas flow rate is about 20% of the gas source inlet flow rate). Under this process condition, the adsorption and desorption performance of the honeycomb molecular sieve can reach the best, that is, the best desorption condition is: the desorption pressure is -90kPa to -97kPa, and the desorption purge gas flow rate is about 20% of the adsorption process simulation gas inlet flow rate.

[0163] Based on the preparation research of the above honeycomb high-concentration NO2 adsorption capture material, the NO2 adsorption capture material is used for pressure swing adsorption separation of high-concentration NO2, and large-size honeycomb materials can be directly prepared (cross-sectional diameter of 0.1-1m, height of 0.1-1m, honeycomb hole equivalent diameter of 1-3mm). Fig. 9 This is a physical picture. The large-size honeycomb material is used in actual industrial applications, namely the exhaust gas treatment in nuclear industry post-processing plants. It can realize the recovery and reuse of nitrogen oxide-containing exhaust gas in the post-processing plant, greatly reduce the acquisition cost and environmental protection cost of NO2, and at the same time meet the dual needs of NO2 raw material production and exhaust gas denitrification in the post-processing plant, realizing the purification and resource utilization of NO2.

[0164] For the adsorption and purification of high-concentration NO2 gas, the present invention achieves this by increasing the zeolite silicon-aluminum ratio (SiO2 / Al2O3). In the BET test, the high silicon-aluminum ratio adsorbent samples provided by the present invention are all confirmed to have a typical microporous structure, and no obvious hysteresis loop appears, indicating that no aggregated mesopores are formed, showing greater advantages in the adsorption and desorption process. With the increase of SiO2 / Al2O3, the specific surface area of ​​zeolite will also increase, because high SiO2 / Al2O3 will reduce the formation of non-framework aluminum during the material synthesis process. With the increase of SiO2 / Al2O3, rapid nucleation will be promoted and surface etching will be increased, thereby enhancing the acid resistance and hydrophobicity of the material. In the TG test, the mass loss rate of the material remains basically unchanged when the temperature reaches 300°C, which proves that the zeolite molecular sieve with a high silicon-aluminum ratio exhibits excellent thermal stability of the material. This is due to the stable structure of its skeleton. Even if it is calcined for a long time at 300-500°C during the preparation of the integral honeycomb, its crystal structure will not change, and it has extremely strong stability; at the same time, the pore structure of the high-silicon molecular sieve is regular and has a large specific surface area, which provides sufficient adsorption sites and channels for the adsorption of NO2. The pore system composed of the ten-membered ring of the high-silicon molecular sieve with a silicon-aluminum ratio of 1000-5000 has a medium-sized pore diameter (grain size: 1-5μm), which gives it excellent selectivity, which means that only molecules smaller than the crystal pores (such as NO2, etc.) can enter the adsorption site, thereby achieving precise selective adsorption of the size and shape of the adsorbed gas.

[0165] In addition, the adsorption of NO2 is accompanied by the generation of NO. Usually, after high-temperature calcination and dehydration, the synthesized zeolite molecular sieve will cause certain incompleteness in its framework, that is, the oxygen atoms in the zeolite framework Si-O-Al will be separated, resulting in oxygen deficiency and the formation of oxygen vacancies V0. Such oxygen deficiency sites are called Lewis acid sites. NO2 is a highly reactive gas. During the adsorption process, when NO2 approaches these oxygen deficiency sites, it will lose an oxygen atom to repair the oxygen vacancies. The oxygen atoms form covalent bonds with Si and Al and are fixed in the framework, while NO2 will lose an oxygen atom to form gaseous NO. In addition to NO2 repairing oxygen vacancies to form NO gas, in the high silicon molecular sieve adsorbing NO x During the process, NO2 will undergo a disproportionation reaction on the surface of the molecular sieve and will also generate NO gas. On the surface of the molecular sieve, NO2 molecules can polymerize into nitrogen tetroxide (N2O4), and then N2O4 can further undergo a disproportionation reaction to generate NO3 - Ions and NO + Ion, NO + Will bind to the negatively charged position in the zeolite framework, replacing and compensating other cations (which will react with NO3 -At the same time, in this process, due to the redistribution of electrons between nitrogen atoms in the N2O4 molecule, the oxidation state of some nitrogen atoms will be reduced, thus forming NO gas molecules. Therefore, avoiding the molecular sieve from being negatively charged is a way to avoid disproportionation. The negative charge of the molecular sieve framework is due to the introduction of aluminum oxide tetrahedron (Al 3+ To Si 4+ The isomorphic substitution causes the negative charge of the zeolite framework). Therefore, reducing the negative charge of the molecular sieve can avoid the disproportionation reaction as much as possible. The disproportionation reaction will cause NO2 to not be desorbed during the desorption process. The solution to the disproportionation reaction in the present invention is to increase the silicon-aluminum ratio of the adsorbent material and reduce the introduction of aluminum-oxygen tetrahedrons, that is, to use a zeolite molecular sieve with a higher silicon-aluminum ratio (silicon-aluminum ratio of 1000-5000); the adsorbent material is made into a slurry and coated on a honeycomb substrate to make an integral honeycomb-molded molecular sieve, both of which can solve the generation of NO.

[0166] Industrial NO2 adsorption and desorption cycle process needs to meet the requirements of NO2 effective adsorption capacity and desorption gas concentration at the same time. NO2 adsorbent with good performance needs to have deep NO2 purification adsorption performance, water resistance and recyclability. CHA type, BETA type, FAU type and ZSM-5 type zeolite have been confirmed in the present invention that BAS sites have excellent NO2 adsorption and purification performance. The positive holes (Al-O·-Si) on the oxygen atoms connecting Si and Al form BAS sites through the loss of H. For zeolite molecular sieves, accessible BAS sites promote the 2NO+O2→2NO2 process through a series of oxidation reactions. At the same time, the higher the silicon-aluminum ratio of the molecular sieve, the more silicon-oxygen bonds there are, and the silicon-oxygen bonds are stronger than the aluminum-oxygen bonds, forming a more stable skeleton structure, thereby reducing the number of hydrophilic groups Si-OH, directly leading to the enhancement of hydrophobicity, strengthening the competitive adsorption of NO2 and H2O(g), and making the molecular sieve more capable of adsorbing NO2.

[0167] The present invention conducts in-depth research on the adsorption and separation of high-concentration NO2. By performing performance evaluation tests on various types of molecular sieves, the molecular sieve raw powder with better performance required for NO2 adsorption and separation is selected, and then honeycomb molecular sieves are prepared based on the raw powder. In this process, a large amount of preparation formula debugging is required, and finally a high-silicon molecular sieve honeycomb NO2 adsorption capture material and a preparation method with strong adsorption performance, easy desorption performance and good cyclic stability are selected.

[0168] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For ordinary technicians in this field, they can still modify or transform the technical solutions described above, which all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a honeycomb high-concentration NO2 adsorption and capture material, characterized in that: The preparation method comprises: (1) preparing an adsorbent slurry using high silicon molecular sieve powder as raw material; (2) placing the honeycomb carrier into the adsorbent slurry for dipping and coating; (3) The honeycomb carrier treated in step (2) is naturally aired, dried, and calcined to obtain an integral honeycomb high-concentration NO2 adsorption and capture material.

2. The method for preparing a honeycomb high-concentration NO2 adsorption and capture material according to claim 1, characterized in that: In step (1), the raw materials required for preparing the adsorbent slurry include, by weight: 100-1000 parts of water, 2.5-40 parts of thickener, 10-100 parts of binder, 10-100 parts of auxiliary agent, 50-400 parts of high-silicon molecular sieve raw powder and 1-10 parts of weak base reagent; The method for preparing the adsorbent slurry is: (1.1) Weigh 100-1000 parts of water, 2.5-40 parts of thickener, 10-100 parts of binder and 10-100 parts of auxiliary agent in order by mass, mix and stir to form an adsorbent aqueous solution; (1.2) The adsorbent aqueous solution, 50-400 parts of high-silicon molecular sieve raw powder and 1-10 parts of weak base reagent are mixed and stirred to form the adsorbent slurry.

3. The method for preparing a honeycomb high-concentration NO2 adsorption and capture material according to claim 1, characterized in that: The high-silicon molecular sieve includes any one or more of CHA, BETA, FAU and ZSM-5 zeolites; and the silicon-aluminum ratio of the high-silicon molecular sieve is 1000-5000, and the grain size is 1-5 μm.

4. The method for preparing a honeycomb high-concentration NO2 adsorption and capture material according to claim 2, characterized in that: The thickener is any one of hydroxypropyl methylcellulose, carboxymethyl cellulose, and industrial soluble starch; the binder is any one of aluminum sol, attapulgite, and silica sol; the auxiliary agent is any one of ethylenediamine, ammonia water, isopropanolamine, and monoethanolamine; the weak base reagent is any one of ammonia water, copper hydroxide, and iron hydroxide; The viscosity of the adsorbent slurry is controlled to be between 20 and 50 mPa·s, and the pH of the adsorbent slurry is controlled to be between 7.0 and 8.

5.

5. The method for preparing a honeycomb high-concentration NO2 adsorption and capture material according to claim 1, characterized in that: In step (2), the honeycomb carrier is pretreated and then dip-coated; The pretreatment specifically includes: cutting the honeycomb carrier into a desired shape, placing the cut honeycomb carrier into a muffle furnace and heating it to 350-500° C. for pretreatment; the treatment time range is 5-20 hours; In step (2), the honeycomb carrier is placed in the adsorbent slurry for immersion coating for 5-30 minutes.

6. The method for preparing a honeycomb high-concentration NO2 adsorption and capture material according to claim 1, characterized in that: Step (3) is specifically as follows: leaving the impregnated carrier to air-dry for 1-24 hours, drying at 100-250°C for 1-10 hours, and calcining at 200-450°C for 2-40 hours to obtain an integral honeycomb high-concentration NO2 adsorption and desorption material.

7. A honeycomb high-concentration NO2 adsorption and capture material, prepared by the method according to any one of claims 1 to 6, characterized in that: The honeycomb high-concentration NO2 adsorption and capture material includes a honeycomb carrier and a high-silicon molecular sieve loaded on the honeycomb carrier; the high-silicon molecular sieve includes any one or more of CHA type, BETA type, FAU type and ZSM-5 type zeolites, and the silicon-aluminum ratio of the high-silicon molecular sieve is 1000-5000, and the grain size is 1-5μm.

8. The honeycomb high-concentration NO2 adsorption and capture material according to claim 7, characterized in that: The honeycomb high-concentration NO2 adsorption and capture material is a large-sized cylinder with a cross-sectional diameter of 0.1-1m, a height of 0.1-1m, and a honeycomb hole equivalent diameter of 1-3mm.

9. An application of a honeycomb high-concentration NO2 adsorption and capture material, characterized in that: The honeycomb high-concentration NO2 adsorption and capture material described in claim 8 is used for pressure-temperature swing adsorption separation of high-concentration NO2 in flue gas, wherein the volume percentage concentration of NO2 in the flue gas is 0.5%-20%.

10. Application of high-silicon molecular sieve, characterized in that: High-silicon molecular sieves are used for pressure-temperature swing adsorption separation of high-concentration NO2. The high-silicon molecular sieves include CHA, BETA, FAU and ZSM-5 zeolites, and the silicon-aluminum ratio of the high-silicon molecular sieves is 1000-5000, and the grain size is 1-5μm.

Citation Information

Cited By

  • System and method for treating tail gas of CVD (chemical vapor deposition) equipment for depositing silicon carbide coating

    CN121103112A